Cold Exposure Exacerbates the Development of Diabetic Polyneuropathy in the Rat. (30th November 2009) - Kasselman, Lora J.; Veves, Aristidis; Gibbons, Christopher H.; Rutkove, Seward B.
Abstract : Diabetic polyneuropathy (DPN) and cold-induced nerve injury share several pathogenic mechanisms. This study explores whether cold exposure contributes to the development of DPN. Streptozotocin-induced diabetic rats and controls were exposed to a room temperature (23 ∘ C) or cold environment (10 ∘ C). H-reflex, tail and sciatic motor, and sensory nerve conduction studies were performed. Analyses of sural nerve, intraepidermal nerve fibers, and skin and nerve nitrotyrosine ELISAs were performed. Diabetic animals exposed to a cold environment had an increased H-reflex four weeks earlier than diabetic room temperature animals (P = .03 ). Cold-exposed diabetic animals also had greater reduction in motor conduction velocities at 20 weeks (P = .017 ), decreased skin nerve fiber density (P = .037 ), and increased skin nitrotyrosine levels (P = .047 ). Cold exposure appears to hasten the development of DPN in the rat STZ model of diabetes. These findings support that further study into the relationship between ambient temperature and DPN is warranted.